Recent Translations of the Medieval Icelandic Bishops' Sagas - Patzuk-Russell, Ryder C. (Scandinavian-Canadian Studies, 2023)
This article reviews two recent English-language translations of medieval Icelandic bishops’ sagas, and contextualizes them in the history of translations from this genre. Margaret Cormack’s The Saga of St. Jón of Hólar and Theodore M. Andersson’s Bishops in Early Iceland were both published in 2021, and make important contributions to the growing interest in medieval Icelandic ecclesiastical history and religious literature. Cormack’s book provides a more precise translation and is accompanied by a thorough study of the saga and its themes, while Andersson provides a more accessible and approachable if somewhat more limited work. These publications are part of body of new translations in the genre, which has flourish since 2000, after a long period of neglect. Cet article examine deux récentes traductions en anglais de sagas sur des évêques islandais médiévaux, et les place dans le contexte de l’histoire des traductions de ce genre littéraire. Publiés en 2021, The Saga of St. Jón of Hólar de Margaret Cormack et Bishops in Early Iceland de Theodore M. Andersson contribuent fortement à l’intérêt grandissant pour l’histoire ecclésiastique et la littérature religieuse de l’Islande médiévale. Le livre de Cormack offre une traduction plus précise et est accompagné d’une étude minutieuse de la saga et ses thèmes, tandis que Anderson fournit un travail plus accessible et abordable, bien qu’un peu plus limité. Ces publications font partie d’un corpus de nouvelles traductions de ce genre littéraire qui prospère depuis l’an 2000 après une longue période d’oubli.